Hubungan antara Keluhan Kelelahan Subjektif, Umur dan Masa Kerja terhadap Produktivitas Kerja pada Pekerja - Ela Nurdiawati; Rizki Aulia Dina Safira (Universitas Faletehan, 2020)
Work productivity is a measurable result, which can be achieved by someone in a real work environment in each unit of time. The results of a preliminary study of 10 workers, there are 7 workers who have poor work productivity. This study aims to determine the relationship between complaints of subjective fatigue, age and working period with work productivity of workers at PT. KHI Pipe Industries in 2019. The research design used was cross sectional. The study population was all workers at PT. KHI Pipe Industries, amounting to + 205 people. The sample in this study amounted to 75 respondents. The research data found that 77.3% included in the category of moderate work productivity, 68% of respondents have complaints of mild fatigue, the age of the respondents included the old category (82.7%) and the work period included in the moderate category (50.7%). The analysis test shows that there is no relationship between subjective fatigue complaints (Pv = 0.499) on work productivity, there is a relationship between age (Pv = 0,000) and work period (Pv = 0,000) on work productivity.